ANALISIS KELAYAKGUNAAN AIR TANAH DALAM DITINJAU DARI ASPEK KUALITAS DAN GEOLOGI LINGKUNGAN DI KOTA TEMBILAHAN INDRAGIRI HILIR - Muammar Qadafi; Bintal Amin; Muhammad Edisar (Jurnal Ilmu Lingkungan, 2015)
ABSTRACTThis study was conducted to determine the feasibility of groundwater in the Tembilahan city in terms of environmental geology aspect and physic-chemical parameters. The Schlumberger Array of geoelectric technique used to determine the depth and types of aquifers in Tembilahan city, whereasthe quality of ground water determined byLaboratory testing water samples from existing wells. Groundwater that is used by the public is a semi confined groundwater at a depth of 147m to 208m and located under a mudstone layer. Physically the water was slightly yellowish, but odorless, water temperature ranges between 28-34°C, the conductivity ranged from 474-1187μs/cm, and total dissolved solids (TDS) ranging from 50mg/l-726mg/l. Water chemistry parameters analyzed The degree of acidity (pH) ranged from 6.48 to 7.32, hardness as CaCO3 between 21-126m /l, iron (Fe) 0.1-1 mg/l, nitrate 0,0417-0,0604mg/l, sulfur 2-7mg/l and chloride 11-224mg/l. Persistence of chemical parameters of water based on Permenkes No.416/Menkes/Per/IX/1990, the location of aquifers that are under a layer of mudstone causing semi confined ground water in Tembilahan City was not fit for use specially for consumption water.